(untitled) (Texas Journal of Engineering and Technology, 2025)
In the development of the rational technology of purification of prevodchik Uzbek-English ternary Los, it is necessary first of all to take into account the properties of interaction of foreign particles with fibers. The main mass of foreign mixtures of fibrous mass in the primary Los corresponds to fragments of branches or stems on the stalk and dry particles of mulberry tree. With silk fibers, the ilakish strength of the stem branches fluctuates between 1.56 and 2.76 sN teks intervals and mainly depends on the material of the STEM and the hem-budurdig of the surface. The friction coefficient on the surface of plant particles of silk thread is much higher than on the metal surface (except for the straw handle), and the roughness of these Horn surfaces will be higher